Orbital Nature of Carboionic Monoradicals Made from Diradicals - Cárdenas Valdivia, Abel; Dai, Yasi; Rambaldi, Filippo; Barker, Joshua, E.; Dressler, Justin J.; Zhou, Zheng; Zhu, Yikun; Wei, Zheng; Petrukhina, Marina A.; Haley, Michael M.; Casado-Cordón, Juan; Negri, Fabrizia (Wiley, 2023)
The electronic, optical, and solid state properties of a series of monoradicals, anions and cations obtained from starting neutral diradicals have been studied. Diradicals based on s-indacene and indenoacenes, with benzothiophenes fused and in different orientations, feature a varying degree of diradical character in the neutral state, which is here related with the properties of the radical redox forms. The analysis of their optical features in the polymethine monoradicals has been carried out in the framework of the molecular orbital and valence bond theories. Electronic UVVis-NIR absorption, X-ray solid-state diffraction and quantum chemical calculations have been carried out. Studies of the different positive-/negative-charged species, both residing in the same skeletal π-conjugated backbone, are rare for organic molecules. The key factor for the dual stabilization is the presence of the starting diradical character that enables to indistinctively accommodate a pseudo-hole and a pseudoelectron defect with certainly small reorganization energies for ambipolar charge transport.
Keywords: Hidrocarburos; Monoradical cations; Diradicals; Indeno-acenes; Molecular orbitals; Radical anion; Radical cation; ·Redox species; Valence bond structure